Vasyl Ivanovych Makolinets - "Orthopaedics, Traumatology and Prosthetics", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
February 25, 2020 marks the 70th anniversary of the doctor of medical sciences, a well-known physiotherapist, professor at the Institute of Spine and Joint Pathology named after prof. M. I. Sitenko NAMS of Ukraine »Makolinets Vasily Ivanovich.